PERAN EDUKASI DALAM KONSERVASI EKOSISTEM MANGROVE - Hukubun, Ronald Darlly; Lenci Patty, Kristi; Marcia Chara Huwae, Laury; Lunmisay, Jelian; S. Tentua, Caroline (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Mangrove ecosystems are productive ecosystems, and serve as a buffer between land and sea. Fishermen have a very important role in maintaining mangrove ecosystems, they are direct users of the resources in the ecosystem. The purpose of this service activity is to increase public awareness, especially fishermen in Allang Asaude Village about the importance of mangrove ecosystems. Through understanding the importance of mangroves, fishermen can contribute to conservation efforts and sustainable resource management. Effective socialization and education can be seen through changes in attitudes and behaviors of the people of Allang Asaude Village towards mangrove ecosystem conservation. Based on the results of the evaluation that has been carried out, there is an increase in the understanding of fishermen and the community about the function and role of mangrove ecosystems. Thus, the sustainability of mangrove ecosystems is not only important for the environment but also crucial for the welfare of fishermen. With the right understanding and management strategies, as well as active participation from the community, the economic benefits of mangrove ecosystems can be maintained, as well as protecting and maintaining sustainable biodiversity